Dukungan Sosial dengan Tingkat Kecemasan Siswa dalam Menghadapi Ujian Akhir Nasional - Nura Safira Afifa (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Anxiety often happens when will face the test, because the success of students in achieving established criteria also the graduation of students becomes a benchmark in taking the education process to the next level. Anxiety is influenced by several factors, one of them is social support. Social support is very effective in reducing psychological distress, such as depression or anxiety. Purpose: To determine the correlation between social support and the level of anxiety in dealing with national examination for XII grade students at SMA 1 North Raman East Lampung. Method: Using an observational analytical design with a cross-sectional approach. The samples were collected using a purposive sampling technique. Data collection was collected by using the questionnaire and then analyzed them using the Spearman test. Results: There were 78 samples of students class XII, 45 respondents (57.7%) with moderate social support category, and 48 respondents (61.5%) with moderate anxiety level category, Spearman statistical test results obtained p = 0.008 (p <0.05), which means there is a significant relationship between social support and level of anxiety. Conclusion: The final result shows that there is a significant relationship between social support and the level of anxiety.